(related to Fig 5) Effects of PV cell activation on the activity of Pyr cells across the different time windows and task difficulty conditions. - Lilia Kukovska (22683586) (2025)
A) Histogram of stimulus selectivity (positive values: cells prefer rewarded go stimulus; negative values: cells prefer unrewarded no-go stimulus) for pre- and post-learning of the visual discrimination task. Pre: n = 1,147, 10 mice, 0.05 ± 0.02; Post: n = 1,467, 9 mice, 0.14 ± 0.02; p < 0.002 (Wilcoxon rank-sum test). Median ± SEM. B) Average stimulus response activity at different times, ranging from 0 to 120 ms (laser duration), 120–240, 240–360, 360–480, and 480–600 ms, during the early window stimulation (0–120 ms) when stimulating PV cells with highest laser (control subtracted). Error bars, SEM. C) Average responses of two population of neurons (left panel, Pyr cells; right panel; PV cells) to optogenetic laser illumination at three different levels during the entire stimulus duration (0–2 s). The activity to the visual stimulus of Pyr cells (n = 1,156) is suppressed, whereas PV cells (n = 39) is increased. Shading, SEM. D) Difference in mean visual stimulus-evoked response with PV cell activation (control subtracted), aligned to visual stimulus onset (continuous line). Cells were ordered by their averaged activity at 0–1 s. Color bar range indicates activity, with positive values (blue) for cells increasing their activity and negative values (red) for cells decreasing their activity as a result of laser stimulation. E) is same as D) but for difficult task. F) Average activity response to visual stimulus in the absence (black) and presence (red) of laser stimulation, for the entire (left panel) and the early window condition (right panel). G) is same as F) but for difficult task. In plots D) to G): dashed line at 2 s for the entire window and at 0.12 s for the early window marks the laser stimulation offset; data shown for the highest laser power. (TIFF)